ChemInform Abstract: Buchwald—Hartwig Reactions in Water Using Surfactants. Issue 43 (21st October 2014) - Salome, Christophe; Wagner, Patrick; Bollenbach, Maud; Bihel, Frederic; Bourguignon, Jean‐Jacques; Schmitt, Martine
Abstract The scope of the Pd‐catalyzed Buchwald—Hartwig amination of aromatic and heteroaromatic halides with primary and secondary amines, N‐heterocycles and carboxylic amides is investigated using micellar aqueous reaction conditions.